Effect of Financial Performance on Going Concern Audit Opinion - Gisela Indah Krisna Arum,; Ambar Woro Hastuti,; Adi Suprayitno, (International Journal of Research in Social Science and Humanities (IJRSS) ISSN:2582-6220, DOI: 10.47505/IJRSS, 2022)
This study aims is to examine and analyze the effect of financial performance through activity ratios, liquidity ratios, solvency ratios, and profitability ratios on going Concern Audit Opinions. This research is expected to provide benefits of knowledge in the fields of accounting and auditing, add insight to the company about the effect of financial ratios, become the basis or basis for further new research, become a consideration for investors in deciding whether to invest or not, and become a further study of performance on the going concern audit opinion. The research samples were collected from Pharmaceutical Companies and Food and Beverage Companies. Research data was obtained through purposive sampling method and obtained as many as 16 companies. Research data was collected through the method of documentation. The analysis technique used is Binary Logistic Regression. The results showed that the Financial Performance as measured by the Solvency Ratio had a significant effect on the Going Concern Audit Opinion whereas the Financial Performance as measured by the Activity Ratio, Liquidity Ratio, and Profitability Ratio did not significantly affect the Going Concern Audit Opinion.